International migration and crisis : transition toward a new migratory phase - Jardón Hernández, Ana Elizabeth (SpringerBriefs in environment, security, development and peace, 2016)
This book presents an analysis of the various transformation processes at work in the international migratory dynamic of Mexicans as a consequence of the 2008 international economic crisis and the implementation of an increasingly strict American migration policy. Employing a methodology that combines qualitative and quantitative tools, the main findings of this work indicate that the international migration of Mexicans is moving towards a new phase, an era of "contraction and disengagement" that is characterized by the confluence of multiple changes with repercussions on the functioning of international migration as a socioeconomic strategy at the family and migrant community levels. .